Error monitoring and correction in violin performance: An EEG study - Ángel David Blanco; Jordi Costa-Faidella; Alfonso Pérez Carrillo; David Dalmazzo; Rafael Ramirez-Melendez; Iria SanMiguel (NeuroImage)
Previous research using electroencephalography (EEG) has investigated neural error-related music production processes in expert pianists reporting a frontal event-related negativity followed by a P300 event-related potential (ERP) after mistuned notes. However, piano playing does not rely on auditory feedback and corrective movements when dealing with accurate note tuning, thus offering an incomplete picture about error monitoring processes in players of many other musical instruments, including the human voice. We here designed a setup allowing us to collect the EEG of expert bow-string players while performing short melodies on the violin, (a fretless instrument) while also manipulating in real-time the produced pitch in a controlled manner. 15 expert bow-string players were asked to 1) listen to a reference melody of four notes; 2) play that melody with a violin (Active Condition); and 3) listen passively to the replay of their performance (Replayed Condition). Randomly, the auditory feedback of one of the four melody notes was manipulated in the Active Condition by lowering or lifting the pitch by half semitone. We found that mistuned notes, independently of whether they were manipulated externally or were produced by natural playing errors, elicited an f-ERN followed by a P300. We also found that the amplitude of the f-ERN was larger for faster corrective movements than for slower ones. In addition, between the f-ERN and the P300, we also identified two negative components—one in parietal areas and another in central-right regions—whose amplitudes were greater for slower corrective movements. We suggest the existence of two error-monitoring systems: a ''fast'' system mediated by the medial frontal cortex that quickly corrects errors when certainty is high and a ''slow'' system mediated by the posterior parietal cortex that accumulates evidence under uncertainty before triggering correction.